2019
DOI: 10.1017/jfm.2019.163
|View full text |Cite
|
Sign up to set email alerts
|

Resolvent-analysis-based design of airfoil separation control

Abstract: We combine three-dimensional (3D) large-eddy simulations (LES) and resolvent analysis to design active separation control techniques on a NACA 0012 airfoil. Spanwiseperiodic flows over the airfoil at a chord-based Reynolds number of 23, 000 and a freestream Mach number of 0.3 are considered at two post-stall angles of attack of 6 • and 9 • . Near the leading edge, localized unsteady thermal actuation is introduced in an open-loop manner with two tunable parameters of actuation frequency and spanwise wavelength… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
102
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(110 citation statements)
references
References 67 publications
8
102
0
Order By: Relevance
“…The mode shapes for intermediate frequencies have a mix of both linear mechanisms as seen for ω = 12 in figure 16. These results are consistent with Thomareis & Papadakis (2018) and Yeh & Taira (2019), who computed resolvent modes for a NACA 0012 airfoil at similar Reynolds numbers and angles of attack from time-averaged DNS and large-eddy simulation (LES) data, respectively. The latter study also identified two branches in the eigenspectrum of the LNS operator which were grouped into wake or shear layer modes.…”
Section: A10 Case: Multiple Linear Mechanismssupporting
confidence: 87%
See 1 more Smart Citation
“…The mode shapes for intermediate frequencies have a mix of both linear mechanisms as seen for ω = 12 in figure 16. These results are consistent with Thomareis & Papadakis (2018) and Yeh & Taira (2019), who computed resolvent modes for a NACA 0012 airfoil at similar Reynolds numbers and angles of attack from time-averaged DNS and large-eddy simulation (LES) data, respectively. The latter study also identified two branches in the eigenspectrum of the LNS operator which were grouped into wake or shear layer modes.…”
Section: A10 Case: Multiple Linear Mechanismssupporting
confidence: 87%
“…where s is a complex number with nonzero real part. Yeh & Taira (2019) applied the discounted resolvent to flow around a NACA 0012 airfoil since they encountered unstable modes. Since we do not find unstable eigenmodes near the wake frequencies, we opt to not apply this procedure.…”
Section: Modelling Of the A10 Velocity Fluctuationsmentioning
confidence: 99%
“…,q k ] contains a set of left singular vectorsq j called the response modes, and The resolvent gain is studied in the context of having an energy norm defined by E = ∫ S (|ρ| 2 + |ρu| 2 + |ρv| 2 + |ρw| 2 + |ê| 2 )dA = ||q|| 2 E in the present work. This norm can be related to the induced 2-norm of the resolvent operator H(q; ω, β) through a weight matrix W, such that ||q|| 2 E = ||Wq|| 2 2 [11,28]. The weight matrix W can be constructed based on the discretization scheme adopted in the numerical configuration.…”
Section: Resolvent Analysismentioning
confidence: 99%
“…Because of the weight matrix W used in the induced 2-norm evaluation, the resulting forcing and response modes shown later have been scaled by W −1 to represent the correct flow field. Details on the norms can be found in Yeh & Taira [11].…”
Section: Resolvent Analysismentioning
confidence: 99%
“…For example, under the correct scaling of the wall-parallel wavenumbers, the self-similar hierarchies of response modes give rise to self-similar families of vortical structures. However, there has been less work applying this operator based decomposition to fully-developed compressible flows, with the exception of the recent studies on compressible jet flows (Jeun et al 2016;Towne et al 2018;Schmidt et al 2018), subsonic aerofoils (Yeh & Taira 2019), turbulent Couette flows (Dawson & McKeon 2019), and hypersonic boundary layer transitions (Cook et al 2018;Dwivedi et al 2018).…”
Section: Introductionmentioning
confidence: 99%